Community Participation in Manyaran Village, Banyakan Subdistrict, Kediri District in the Kampung Keluarga Berkualitas Program - Sari, Irla Rahma; Pertiwi, Vidya Imanuari (Universitas Muhammadiyah Ponorogo, 2025)
Kampung Keluarga Berkualitas (KB) in Manyaran Village was established in response to the challenges faced by the community, namely the low awareness of the importance of using long-term contraceptives and the prevalence of marriage at a young age. This study aims to determine the active participation of Manyaran Village community in the Quality Family Village program. This study uses Cohen and Uphoff's theory of community participation to look at community participation in four stages: when making decisions, when carrying out activities, when utilizing program results, and when evaluating the program. This research uses qualitative methods by collecting data through interviews, observations, and documents. The results showed that: 1) Decision Making: The community has not been fully involved in decision-making, especially during meetings; 2) Activity Implementation: Tribina Kampung KB activities have not been implemented evenly in all hamlets; 3) Utilization of Results: The community benefits from additional food for children, vitamins, and new knowledge about the family. In addition, the establishment of Rumah Data Ku also provides social benefits; 4) Evaluation: The community has not actively participated in evaluating the program.